Green synthesis of silver nanoparticles using coffee extract for catalysis - Alafandi, Lama; Nasaruddin, Ricca Rahman; Abdul Aziz, Ainul Husna; Engliman, Nurul Sakinah; Mastuli, Mohd Sufri (University Malaya - NANOCAT, 2021)
The green synthesis method for producing metal nanoparticles has become more popular because it is more environmentally friendly and low cost. This study used a green approach to synthesize silver nanoparticles (AgNPs) using coffee Arabica bean's extract to reduce and stabilizing agents. The coffee extract was analyzed using GC-MS to identify the bioactive compounds in the extract, and Folin-Ciocalteu colorimetric test was done to find the total phenols in the extract. Later, the extract was used in the synthesis of AgNPs. Effects of synthesis parameters such as temperature, reaction time, pH, and amount of coffee extract on the formation of AgNPs were investigated. The formation of AgNPs was mainly observed using UV-Vis absorption spectroscopy. It was found that pH influenced the size of particles produced in which higher pH produce smaller particles than lower pH while other synthesis parameters mainly affected the yield of the AgNPs. The catalytic application of as-synthesized AgNPs was then evaluated in reducing methylene blue (MB) dye in a solution using NaBH4 as a reducing agent. The results show that the green-synthesized AgNPs were capable of catalyzing the reduction of MB dye in the solution